2013
DOI: 10.4103/0022-3859.113825
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fibromyalgia on bone mineral density in patients with fibromylagia and rheumatoid arthritis

Abstract: In spite of functional disability, FM does not cause a decrease in BMD. The presence of FM in RA patients does not result in a change in BMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…The majority of studies were based in single rheumatology departments or clinics [ 11 , 14 , 17 , 18 , 20–22 , 24–29 , 31–33 , 35 , 36 , 37 , 38 , 40 , 41 , 43 , 46–50 , 52 ], some studies used participants from multiple sites or centres [ 30 , 34 , 39 , 42 , 53 ], and some had many centres contributing to a single registry or database [ 13 , 19 , 23 , 45 ]. Study setting also varied by country with five each from the UK [ 14 , 32 , 34 , 36 , 45 ] and the USA [ 18 , 19 , 31 , 39 , 53 ], four each from Brazil [ 21 , 22 , 37 , 18 ] and Italy [ 42 , 43 , 50 , 52 ], three from Egypt [ 26 , 28 , 35 ], France [ 24 , 27 , 46 ] and Turkey [ 11 , 20 , 49 ], two from Denmark [ 23 , 33 ], Israel [ 47 , 51 ], Spain [ 13 , 40 ] and Pakistan [ 17 , 41 ], and one each from Australia […”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of studies were based in single rheumatology departments or clinics [ 11 , 14 , 17 , 18 , 20–22 , 24–29 , 31–33 , 35 , 36 , 37 , 38 , 40 , 41 , 43 , 46–50 , 52 ], some studies used participants from multiple sites or centres [ 30 , 34 , 39 , 42 , 53 ], and some had many centres contributing to a single registry or database [ 13 , 19 , 23 , 45 ]. Study setting also varied by country with five each from the UK [ 14 , 32 , 34 , 36 , 45 ] and the USA [ 18 , 19 , 31 , 39 , 53 ], four each from Brazil [ 21 , 22 , 37 , 18 ] and Italy [ 42 , 43 , 50 , 52 ], three from Egypt [ 26 , 28 , 35 ], France [ 24 , 27 , 46 ] and Turkey [ 11 , 20 , 49 ], two from Denmark [ 23 , 33 ], Israel [ 47 , 51 ], Spain [ 13 , 40 ] and Pakistan [ 17 , 41 ], and one each from Australia […”
Section: Resultsmentioning
confidence: 99%
“…Amongst the studies that reported disease activity, common reasons for lower scoring were poor description of statistical methods, non-blinding of examiners and important differences between comparison groups. Gender, age and disease duration were well reported in the included studies and 19 papers were assessed as lower quality due to differences between comparison groups for at least one of these factors [ 11 , 13 , 14 , 20 , 22 , 24 , 34 , 36 , 37 , 38 , 40 , 43 , 46–52 ]. Other confounding factors may have been important, but amount of comorbidity and treatment regimen were reported only in a small number of studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Die "weichen" Klassifikationskriterien der Erkrankung und das Fehlen eindeutiger diagnostischer Kriterien führt bei vielen Medizinern zu einer geringen Akzeptanz der Erkrankung, die Diagnose FMS ist daher an sich immer wieder umstritten [7]. [9,10]. Die Vielschichtigkeit des Krankheitsbildes sowie die häufig von den Patienten geäußerten multiplen Beschwerden führen in vielen Fällen zu multiplen Arztbesuchen mit einer daraus resultierenden umfangreichen Diagnostik ( • ▶ Abb.…”
Section: Abstract ▼unclassified